Perlindungan terhadap Satwa Endemik yang Dilindungi Berdasarkan Undang-Undang No. 5 Tahun 1990 Tentang Konservasi Sumber Daya Alam Hayati dan Ekosistemnya - Prasetyo Hadi; Didik Suhariyanto; Dewi Iryani (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Animal protection must be developed as a counterweight to the democratic system developed by humans. The concept of animal protection can be understood in the context of a balanced relationship between God, nature and humans. So far, power relations have only been seen as a human problem. In democracy, only humans, called the people, are made the starting point and center of attention, which will lead to massive exploitation of nature.The research method used is the Normative Juridical research type, in accordance with the objectives the author wants to achieve, the methodology in designing the thesis research uses two types of approaches, namely the Statutory Approach and the Conceptual Approach. The Statute Approach is an approach carried out by examining all laws with the concept of law. Authority for Endemic Animals Protected in the Conservation of Biological Natural Resources and Their Ecosystems, Based on the material regulated in this Law, Law no. 5 of 1990 contains fundamental weaknesses, namely: It only categorizes types into protected and unprotected. For protected species, the provisions regarding sanctions for violations are clearly regulated and adequate.Legal Protection of Endemic Animals which are Protected Based on Law Number 5 of 1990 Conservation of Living Natural Resources and Their Ecosystems, Regulations that regulate the balance between utilization and balancing must also be balanced. It must always be controlled to maintain forest stability